A new species of the genus Hydroporus Clairville, 1806 from the Central Rif mountains of northern Morocco (Coleoptera: Dytiscidae) - Manuel, Michael (Zootaxa, 2014)
Hydroporus rifensis sp. n. is described from Central Rif in northern Morocco. The new species is the first member of the Hydroporus tristis-group to be recorded from the African continent. Analyses of cytochrome oxydase 1 (CO1) and 16S rRNA partial sequences indicate unambiguously that H. rifensis sp. n. is a geographical vicariant of the widespread and common European species Hydroporus gyllenhalii Schiödte, 1841, whose closest Iberian populations are known from southern Spain and southern Portugal. Genetically the two species are very close, but in terms of morphology they differ considerably, to the extent that in several respects H. rifensis sp. n. is more similar to some species of the H. striola-group, the sister clade of the H. tristis-group. The new species differs from H. gyllenhalii notably by its larger size, lighter elytra, stronger pubescence, much finer elytral punctation, morphology of the median prosternum area, and marked differentiation of protarsal claws in male. Hydroporus rifensis sp. n. is the first dytiscid species endemic to the Rif and the second Hydroporus species endemic to Morocco.